2013
DOI: 10.1093/jnci/djs494
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Ovarian Cancer Survival Associated With Mutation in BRCA1 or BRCA2

Abstract: For women with invasive ovarian cancer, the short-term survival advantage of carrying a BRCA1 or BRCA2 mutation does not lead to a long-term survival benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
5
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 16 publications
11
98
5
6
Order By: Relevance
“…Additional investigators confirmed the above findings by showing that patients with BRCA mutation-related (hereditary) epithelial ovarian cancer exhibited improved PFS, OS as well as increased sensitivity to platinum agents in the adjuvant setting [18][19][20][21][22][23][24].…”
Section: Brca1 and Brca2mentioning
confidence: 73%
“…Additional investigators confirmed the above findings by showing that patients with BRCA mutation-related (hereditary) epithelial ovarian cancer exhibited improved PFS, OS as well as increased sensitivity to platinum agents in the adjuvant setting [18][19][20][21][22][23][24].…”
Section: Brca1 and Brca2mentioning
confidence: 73%
“…To ensure that a clinical study is reliable, it is important that most patients be followed for a long period, ideally for 10 or more years. Studies based on shorter follow-up periods (5 years, say) may lead to erroneous conclusions even if the total number of person-years is large-a situation similar to that with ovarian cancer 6,7 . Screening studies and studies involving clinical interventions can both potentially be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Following classic tumor suppressor gene kinetics, BRCA1-and BRCA2-induced carcinogenesis result from a "second hit" somatic mutation(s) in the normal allele, leading to loss of BRCA function [21] and homologous DNA recombination deficiency (HRD). This HRD state, though carcinogenic, can paradoxically confer sensitivity to platinum and other DNA-damaging cytotoxics, as well as PARP inhibitors [22,23].Several studies have reported better prognosis for women with BRCA-mutated ovarian cancer, especially BRCA2, possibly secondary to the improved platinum response [22][23][24][25][26][27]. Other genes in the HR pathway such as RAD51C, RAD51D, BRIP1, PALB2, and BARD1, may also influence ovarian cancer risk and biology [28][29][30].…”
Section: The Importance Of Genetic Testing In Cancer Care Deliverymentioning
confidence: 99%